2020
DOI: 10.5187/jast.2020.62.4.429
|View full text |Cite
|
Sign up to set email alerts
|

The study on estimated breeding value and accuracy for economic traits in Gyoungnam Hanwoo cow (Korean cattle)

Abstract: This study was conducted to construct basic data for the selection of elite cows by analyzing the estimated breeding value (EBV) and accuracy using the pedigree of Hanwoo cows in Gyeongnam. The phenotype trait used in the analysis are the carcass weight (CWT), eye muscle area (EMA), backfat thickness (BFT) and marbling score (MS). The pedigree of the test group and reference group was collected to build a pedigree structure and a numeric relationship matrix (NRM). The EBV, genetic parameters and accuracy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…While the genetic correlation of EMA and BFT using PBLUP and GBLUP each being -0.02 ± 0.07 and −0.06 ± 0.03, the established correlation is negative while this is positive for all other traits. Looking at previous research, the genetic and phenotypic correlation in PBLUP value reported by Kim et al (2020) and the results of this study are the same, because they use the same reference group. According to the research by Kim et al (2010), the genetic correlation of EMA, BFT and MS concerning CWT was 0.61, 0.19 and 0.08, of BFT and MS with BFT as -0.22 and 0.17 and of BFT and MS as 0.05, which were similar to this study.…”
Section: Basic Statistics Analysis Of Reference Groupsupporting
confidence: 64%
See 4 more Smart Citations
“…While the genetic correlation of EMA and BFT using PBLUP and GBLUP each being -0.02 ± 0.07 and −0.06 ± 0.03, the established correlation is negative while this is positive for all other traits. Looking at previous research, the genetic and phenotypic correlation in PBLUP value reported by Kim et al (2020) and the results of this study are the same, because they use the same reference group. According to the research by Kim et al (2010), the genetic correlation of EMA, BFT and MS concerning CWT was 0.61, 0.19 and 0.08, of BFT and MS with BFT as -0.22 and 0.17 and of BFT and MS as 0.05, which were similar to this study.…”
Section: Basic Statistics Analysis Of Reference Groupsupporting
confidence: 64%
“…Looking at previous research that estimated genetic trend using pedigree, the heritability of carcass trait reported by Kim et al (2020) and the results of this study are the same, because they use the same reference group. 2013) reported the heritability of EMA, BFT and MS as 0.46, 0.60 and 0.63 for progeny test cattle, which was higher than the results of this study.…”
Section: Basic Statistics Analysis Of Reference Groupmentioning
confidence: 69%
See 3 more Smart Citations